Biometry of the skull of Buffalo (Bubalus bubalis) - Sasan, Jasvinder Singh; Sarma, Kamal; Suri, Shalini; Malik, M R (Indian Journal of Veterinary Anatomy, 2018)
The present study was conducted on skull of eleven indigenous buffaloes obtained from different sources. The length (52.50 ± 1.66 cm) of the skull was approximately two and half times in comparison to its width (21.50 ± 1.09cm) with cephalic index of 41. The nuchal crest and torus frontalis were not conspicuous. Facial crest and facial grooves were indistinct. The orbit was circuloid and measured 23.00 ± 0.782 cm2 in area. The frontal bone formed largest (45.00 %) part of the orbital rim. The maxillary part of the skull was one and half times (60.00 cm) to that of the cranial part (40.00 cm).